A Review Study on Phytochemistry and Pharmacology Applications of Juglans Regia Plant - Delaviz, Hamdollah; Mohammadi, Jamshid; Ghalamfarsa, Ghasem; Mohammadi, Bahram; Farhadi, Naser (Pharmacognosy Reviews)
In recent years, the use of medicinal plants increased considerably; so that today, the use of traditional medicine, as well as medicinal plants is necessary for the aim of producing more effective drugs with fewer side effects and determining the effective doses. With the scientific name of Juglans regia, walnut plant is a medicinal plant with different properties that is considered less, despite having great therapeutic potential in the traditional medicine. The aim of this study was to review the dispersal of walnut plants, the chemical compounds, and therapeutic effects of walnuts on antioxidant activity, antidiabetic, hypolipidemic, antimicrobial, and antihypertensive activities, as well as liver protection. Data of this review study have been collected from the books and scientific articles published in databases such as Science Direct, Web of Science, Scopus, PubMed, and Scientific Information Database. While this plant having high antioxidant capabilities, walnuts are composed of many chemical compounds such as ascorbic acid, flavonoids, quercetin, and caffeic acid. Experimental studies have shown that walnuts reduced blood glucose and lipids and also decreased blood pressure. They have antioxidant, antidiabetic, antimicrobial, and liver‑protective properties. The use of walnuts in traditional medicine and review of experimental studies demonstrated the presence of multiple, effective, and useful compounds which may provide the opportunity for the production of lipid‑lowering, antidiabetes, and liver protective drugs. Due to the effects of walnuts on improving the complications of various diseases, the need for doing comprehensive clinical trials for the use of walnuts in the treatment of diseases is necessary.
Keywords: Antidiabetic; antihypertensive; antioxidant; Juglans regia; pharmacology